1996
DOI: 10.1177/003151259608200301
|View full text |Cite
|
Sign up to set email alerts
|

Height and Perceived Competence of U.S. Presidents

Abstract: The 4 “great” U.S. Presidents, as listed in the 1982 Murray-Blessing Poll, were significantly taller ( M = 74.63 in.) than the 5 considered “failures” ( M = 70.80 in.), consistent with previous research on height and status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 1 publication
1
37
0
Order By: Relevance
“…Recent studies (Yee & Bailenson, 2007;Yee, Bailenson, & Ducheneaut, 2009) showed that participants who saw themselves represented with taller avatars were more aggressive in negotiation tasks than those with short avatars, both inside of the virtual environment as well as in subsequent negotiations face-to-face. This suggests that the participants felt the same confidence that is attributed to tall people in real life (Stogdill, 1948;Young & French, 1996). In separate studies, participants with attractive avatar representations approached a virtual confederate more closely and were more disclosing than participants with avatars of average appearance (Yee & Bailenson; Yee, Bailenson, & Ducheneaut).…”
Section: Variability In Virtual Human Featuresmentioning
confidence: 85%
“…Recent studies (Yee & Bailenson, 2007;Yee, Bailenson, & Ducheneaut, 2009) showed that participants who saw themselves represented with taller avatars were more aggressive in negotiation tasks than those with short avatars, both inside of the virtual environment as well as in subsequent negotiations face-to-face. This suggests that the participants felt the same confidence that is attributed to tall people in real life (Stogdill, 1948;Young & French, 1996). In separate studies, participants with attractive avatar representations approached a virtual confederate more closely and were more disclosing than participants with avatars of average appearance (Yee & Bailenson; Yee, Bailenson, & Ducheneaut).…”
Section: Variability In Virtual Human Featuresmentioning
confidence: 85%
“…Thus, biological traits, such as height, deserve a more prominent role in leadership theories (Bass, 2008;Bass & Riggio, 2006;Murray & Schmitz, 2011). The perception of increased leadership qualities in taller individuals is in line with the higher perceived competence associated with increased stature (Young & French, 1996). The 'halo' effects of increased stature are therefore likely to lead to discrimination in favor of taller men and to the detriment of shorter men .…”
Section: Discussionmentioning
confidence: 99%
“…In light of self-perception theory, just as participants in black uniforms infer an aggressive disposition and in turn behave more aggressively, participants in attractive avatars may infer a friendly and extraverted disposition and behave in a friendlier manner. And in the case of avatar height, given that taller people are perceived to be more confident and more likely to be in positions of power (Stogdill, 1948;Young & French, 1996), participants in taller avatars may conform to those expectations. Thus in general, we may expect users to make inferences about their expected dispositions from their avatar's appearance and then conform to the expected attitudes and behavior, a phenomenon that has been referred to as the Proteus effect .…”
Section: The Proteus Effectmentioning
confidence: 99%
“…The participant and the confederate were asked to split a hypothetical pool of $100 in alternating rounds. given that taller people are perceived to be more confident (Young & French, 1996), it was hypothesized that users in taller avatars would conform to this expectation, and be more aggressive in making splits in their own favor and less likely to yield to unfair splits made against them than users in shorter avatars. The experimenters found that participants in taller avatars offered significantly more unfair splits (in their own favor) than participants in shorter avatars.…”
Section: The Proteus Effectmentioning
confidence: 99%